2013
DOI: 10.1007/s12325-013-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Two Innovative Pharmaceutical Forms of Leuprorelin: Results from 818 Patients with Advanced Prostate Cancer

Abstract: These results confirm the efficacy, tolerability, and ease of use of the leuprorelin implants among a large population of men with advanced, hormone-dependent prostate cancer treated in a clinical practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 10 publications
2
27
0
1
Order By: Relevance
“…The recurrent injection site reactions experienced by all 10 Finnish patients who initially received degarelix could be attributed to the associated histamine release from mast cells, which has been associated with all LHRH antagonists [13]. The data reported here for men switching from degarelix to the leuprorelin acetate implant are consistent with other switching experiences between LHRH analogues in terms of efficacy and safety [6, 8, 10] as well as the potential for associated for cost savings [1]. …”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The recurrent injection site reactions experienced by all 10 Finnish patients who initially received degarelix could be attributed to the associated histamine release from mast cells, which has been associated with all LHRH antagonists [13]. The data reported here for men switching from degarelix to the leuprorelin acetate implant are consistent with other switching experiences between LHRH analogues in terms of efficacy and safety [6, 8, 10] as well as the potential for associated for cost savings [1]. …”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have also reported LHRH agonists and LHRH antagonists to be generally well tolerated (with most adverse events being consistent with androgen suppression or the underlying condition), with the exception of reactions at the injection site with LHRH antagonists [48]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Damit ist Leuprorelin seit über 30 Jahren das führende GnRH-Analogon und bildet die Grundlage für viele multimodale Therapiekonzepte [11]. Neben der langjährigen Erfahrung der Ärzte mit dem Wirkstoff unterstützen auch sehr umfassende Daten zur Wirksamkeit und Sicherheit von Leuprorelin dessen Einsatz [12,13,14].…”
Section: Diskussionunclassified